2015
DOI: 10.4081/ijas.2015.3889
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Crude Protein Digestibility of Tenebrio Molitor and Hermetia Illucens Insect Meals and its Correlation with Chemical Composition Traits

Abstract: The aims of this study were to evaluate the correlation between in vitro crude protein digestibility coefficients of insect meals from Tenebrio molitor (TI) and Hermetia illucens (HI) and their chemical composition traits as well as to develop regression equations able to estimate the in vitro crude protein digestibility (CPd) from proximate analysis of insect meals. Twelve samples of insect meals (6 from TM larvae, TM 1-6 and 6 from HI larvae, HI 1-6) were obtained from different producers and analysed for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
209
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(225 citation statements)
references
References 23 publications
11
209
3
2
Order By: Relevance
“…Chitin is not degraded and absorbed in the small intestine (Vidanarachchi et al, 2010) and thus can affect protein digestibility (Bovera et al, 2015). This is in agreement with Marono et al (2015), who indicated chitin as the main factor affecting the in vitro protein digestibility of insect meals. However, further investigations need to clarify this point.…”
Section: Free Radical Scavenging Activitysupporting
confidence: 54%
See 1 more Smart Citation
“…Chitin is not degraded and absorbed in the small intestine (Vidanarachchi et al, 2010) and thus can affect protein digestibility (Bovera et al, 2015). This is in agreement with Marono et al (2015), who indicated chitin as the main factor affecting the in vitro protein digestibility of insect meals. However, further investigations need to clarify this point.…”
Section: Free Radical Scavenging Activitysupporting
confidence: 54%
“…This is in agreement with Marono et al . (), who indicated chitin as the main factor affecting the in vitro protein digestibility of insect meals. However, further investigations need to clarify this point.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to indicate that insect meals are well digested by seabass. These in vivo ADC data are considerably higher than the in vitro crude protein digestibility determined for H. illucens and T. molitor determined by Marono et al (2015), which ranged from 65.8 to 68.7%. This indicates that the in vitro method may not be adequate for estimating the ADC of protein for fish (Gomes et al 1998;Moyano et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 47%
“…For BSFLM samples, the amount of protein linked to ADF was determined and used to estimate the amount of chitin. According to Marono et al (2015), chitin (%) = ash free ADF (%) − ADF-linked protein (%). The ADF-linked protein was derived from the concentration of N in ADF residue.…”
Section: Samples Preparation and Chemical Analysesmentioning
confidence: 99%